Capital Levies in Central Europe, 1919-1924 - Rostas, L. (Review of Economic Studies, 1940)
Capital Levies in Central Europe, 1919–1924 L. Rostas L. Rostas Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 8, Issue 1, October 1940, Pages 20–32, https://doi.org/10.2307/2967414 Published: 01 October 1940